Vegetation and lake changes on the southern Taymyr peninsula, northern Siberia, during the last 300 years inferred from pollen and Pediastrum green algae records. - Niemeyer, Bastian; Herzschuh, Ulrike; Pestryakova, Ludmila A (PANGAEA, 2015)
Siberian arctic vegetation and lake water communities, known for their temperature dependence, are expected to be particularly impacted by recent climate change and high warming rates. However, decadal information on the nature and strength of recent vegetation change and its time lag to climate signals are rare. In this study, we present a 210Pb/137Cs dated pollen and Pediastrum species record from a unnamed lake in the south of the Taymyr peninsula covering the period from AD 1706 to 2011. Thirty-nine palynomorphs and 10 morphotypes of Pediastrum species were studied to assess changes in vegetation and lake conditions as probable responses to climate change. We compared the pollen record with Pediastrum species, which we consider to be important proxies of climate changes. Three pollen assemblage zones characterised by Betula nana, Alnus viridis and Larix gmelinii (1706-1808); herbs such as Cyperaceae, Artemisia or Senecio (1808-1879), and higher abundance of Larix pollen (1955-2011) are visible. Also, three Pediastrum assemblage zones show changes of aquatic conditions: higher abundances of Pediastrum boryanum var. brevicorne (1706-1802); medium abundances of P. kawraiskyi and P. integrum (1802-1840 and 1920-1980), indicating cooler conditions while less eutrophic conditions are indicated by P. boryanum, and a mainly balanced composition with only small changes of cold- and warm-adapted Pediastrum species (1965-2011). In general, compositional Pediastrum species turnover is slightly higher than that indicated by pollen data (0.54 vs 0.34 SD), but both are only minor for this treeline location. In conclusion, the relevance of differentiation of Pediastrum species is promising and can give further insights into the relationship between lakes and their surrounding vegetation transferred onto climatic conditions.
Pollen and pediastrum record from the southern Taymyr peninsula, northern Siberia
Keywords: AWI_PerDyn; Permafrost Research (Periglacial Dynamics) @ AWI